The Role Of Flexible Work Arragement, Job Embeddedness And Work Life Balance In Reducing Turnover Intention (Study on Millennial Generation and Generation Z Employees at Non-Bank Financing Companies in Multifinance Financing Companies, Jakarta Head Office) - Rosita, Ferriyal; Noermijati, Noermijati; Setiawan, Margono; Susilowati, Christin (Journal of The Community Development in Asia, 2024)
Human resources (HR) are an important component in the success of a company (Dessler, G., 2019).Therefore, managing and maintaining human resources is the most important key for companies to achieve their goals with various challenges in managing human resources and increasingly dynamic business dynamics (Wynne et al., 2021).New challenges after the Covid-19 pandemic and the Millennial Generation and Generation Z who are entering productive age are expected to contribute positively to the nation's progress due to the composition and dominance of the largest population. However, the reality is contrary to these estimates. where the number of millennials and some generation z who enter productive age is increasing and has dominated many jobs and is followed by an increase in turnover rates. High turnover rates exceeding the global average of 13% make organisations required to continue to improve.This study investigate the role of flexible work arrangements, Job Embeddedness and Work Life Balance in suppressing turnover intention in the millennial generation and generation Z in a finance company at the Jakarta headquarters.This research is quantitative research with Non probability. The questionnaire was distributed to employees at the headquarter multifinance company in Jakarta with 280 respondents. The data analysis technique uses Partial Least Square (PLS) analysis tools.The results in this research indicate that Flexible work arrangement (FWA) has a significant negative impact on turnover intention. Flexible work arrangement has a significant positive impact on job embeddedness and work-life balance.Flexible Work Arragement (FWA) has a significant negative impact on Turnover intention which is partially intervening by job embeddedness and work-life balance.